The phraseology in teaching Spanish as a foreign language (SFL). Is it a challenge? An approach to Phraseodidactics - Szyndler, Agnieszka (Didáctica. Lengua y Literatura, 2016)
The aim of this article is to give a general overview of Phraseodidactics, a relatively new discipline which, nowadays, thanks to a large number of papers focusing on different aspects of language teaching, has become an independent field of study. Thus, not only do we explain the notion of ‘Phraseodidactics’, but also we analyze its evolution and objectives. In addition, we present the reasons why phraseology should be considered a vital element while teaching Spanish as a foreign language. Moreover, we investigate various phraseological aspects that can hinder the work of the teachers and the learning process of the students. Finally, based on the developed ideas, we offer general methodological considerations with interesting educational implications.
Keywords: didactic of phraseology; teaching and learning process of phraseology; phrasems; Spanish as a foreign language.